ChemInform Abstract: Pd(II)‐Catalyzed C—H Functionalizations Directed by Distal Weakly Coordinating Functional Groups. Issue 37 (September 2015) - Li, Gang; Wan, Li; Zhang, Guofu; Leow, Dasheng; Spangler, Jillian; Yu, Jin‐Quan
Abstract The direct ortho‐C(sp2)‐H olefination or acetoxylation of phenylacetyl Weinreb amides, esters, and ketones as well as structurally closely related substrates is developed without the need for a directing group.